2020
DOI: 10.1142/s0219477521500115
|View full text |Cite
|
Sign up to set email alerts
|

Man in the Middle and Current Injection Attacks Against the KLJN Key Exchanger Compromised by DC Sources

Abstract: This study addresses a new question regarding the security of the Kirchhoff-Law-Johnson-Noise (KLJN) scheme compromised by DC sources at Alice and Bob: What is the impact of these parasitic sources on active attacks, such as the man-in-the-middle (MITM) attack, or the current injection attack if Alice and Bod did not eliminate these sources? The surprising answer is that the parasitic DC sources actually increase the security of the system because, in the case of the MITM attack, they make easier to uncover th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Several potential security vulnerabilities of the KLJN system have been addressed in previous research [4,42,[73][74][75][76][77][78][79][80][81][82][83][84][85][86]. However, in each case it was shown that these attacks do not compromise the unconditional security of the KLJN scheme because, similarly to quantum encryption, the information leak can be eliminated by defense hardware and privacy amplification.…”
Section: { } M a Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Several potential security vulnerabilities of the KLJN system have been addressed in previous research [4,42,[73][74][75][76][77][78][79][80][81][82][83][84][85][86]. However, in each case it was shown that these attacks do not compromise the unconditional security of the KLJN scheme because, similarly to quantum encryption, the information leak can be eliminated by defense hardware and privacy amplification.…”
Section: { } M a Bmentioning
confidence: 99%
“…In a subsequent work [78], additional security risks of these DC sources were studied under two active attacks: the man-in-the-middle attack and the current-injection-attack. The conclusion of these analyses is that parasitic DC sources do not increase the feasibility and information leak related to these active attacks.…”
Section: Loop Current Attacksmentioning
confidence: 99%
See 1 more Smart Citation
“…74 In the vast body of literature, similarly to the field of QKD, there are attacks, defense techniques, and debates about them. Some of the attacks utilize non-ideal component features that can cause miniscule information leak which can be nullified [75][76][77][78][79][80][81][82][83][84][85][86] by design and/or privacy amplification. 43,52 Some attacks are invalid, (e.g.…”
Section: The Kirchhoff-law-johnson-noise (Kljn) Key Exchangementioning
confidence: 99%